Unplanned pregnancy in Brazil: national study in eight university hospitals - Nilson, Tainá Vieira; Amato, Angélica Amorim; Resende, Ceres Nunes; Primo, Walquíria Quida Salles Pereira; Nomura, Roseli Mieko Yamamoto; Costa, Maria Laura; Opperman, Maria Lúcia; Brock, Marianna; Trapani, Alberto; da Costa Damasio, Lia Cruz Vaz; Reis, Nadia; Borges, Vera [UNESP]; et al. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
OBJECTIVE: To estimate the prevalence of unplanned pregnancy in eight public university hospitals, distributed in the five regions that make up Brazil. METHODS: A secondary analysis of a national multicenter cross-sectional study, carried out in eight public university hospitals between June 1 and August 31, 2020, in Brazil. Convenience sample including women who gave birth within sixty consecutive days and met the following criteria: over 18 years old; gestational age over 36 weeks at delivery; with a single and live newborn, without malformations. RESULTS: Sample composed of 1,120 postpartum women, of whom 756 (67.5%) declared that the pregnancy had not been planned. The median prevalence of unplanned pregnancy was 59.7%. The prevalence of unplanned pregnancy across hospitals differed significantly: Campinas (54.8%), Porto Alegre (58.2%), Florianópolis (59%), Teresina (61.2%), Brasília (64.3%), São Paulo (64.6%), Campo Grande (73.9%) and Manaus (95.3%) (p < 0.001). Factors significantly associated with unplanned pregnancy were maternal age, black color, lower family income, greater number of children, greater number of people living in household, and not having a partner. CONCLUSION: In the studied sample, about two thirds of the pregnancies were declared as unplanned. The prevalence of unplanned pregnancies was related to social and demographic factors and varied significantly across the university hospitals evaluated.
Keywords: Family Development Planning; Hormonal Contraception; Reproductive Rights; Unplanned Pregnancy